Anmeldelser - Staehelin, Martin (Danish Yearbook of Musicology, 1997)
Review of: Peter Woetmann Christoffersen: French Music in the Early Sixteenth Century. Studies in the music collection of a copyist of Lyons. The manuscript Ny kgl. Samling 1848 2o in the Royal Library, Copenhagen 1-3. Museum Tusculanum Press, København 1994.